MANAGEMENT OF GLOBAL DIVERSITY CHARACTER BUILDING PROGRAMS THROUGH P5PPRA AT MAN BINJAI CITY - San Putra; Robin Sirait; Sri Milfa Yetty; Eka Bayu Syahputra (Universitas Islam Negeri (UIN) Sumatera Utara, 2025)
This research aims to explore the planning, implementation, and the supporting and inhibiting factors in the development of global diversity character through the Strengthening Project of Pancasila Student Profiles and Rahmatan lil Alamin Student Profiles (P5PPRA) at MAN Kota Binjai. The background of this study is the growing concern over intolerance and the weakening of national values among the younger generation due to the influence of social media. Using a qualitative ethnographic approach, data were collected through interviews, observations, and documentation, involving school principals, teachers, and students as informants. The results indicate that the P5PPRA project has been systematically planned and contextually implemented to foster tolerance, empathy, and appreciation for diversity among students. Although challenges such as limited facilities and variations in teacher understanding persist, strong institutional support contributes to the program's success. This project has the potential to serve as a replicable model for character education in other Islamic schools.